The Globalization of Foreign Aid : Developing Consensus - Liam Swiss (Routledge, 2018)
Why do aid agencies from wealthy donor countries with diverse domestic political and economic contexts arrive at very similar positions on a wide array of aid policies and priorities? This book suggests that this homogenization of policy represents the effects of common processes of globalization manifest in the aid sector. Drawing on both quantitative and qualitative analysis of policy adoption, the book argues that we need to examine macro-level globalizing influences at the same time as understanding the micro-level social processes at work within aid agencies, in order to adequately explain the so-called ‘emerging global consensus'that constitutes the globalization of aid.The book explores how global influences on aid agencies in Canada, Sweden, and the United States are mediated through micro-level processes. Using a mixed-methods approach, the book combines cross-national statistical analysis at the global level with two comparative case studies which look at the adoption of common policy priorities in the fields of gender and security. The Globalization of Foreign Aid will be useful to researchers of foreign aid, development, international relations and globalization, as well as to the aid policy community.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 license.